Determinants of Students with Disabilities’ Attainment of Graduate/Professional Program Admission Credentials - Miguel, Joyce Ann; Bazzana-Adams, Kayla D.; deBraga, Michael; Kamenetsky, Stuart (Advances in Social Sciences Research Journal, 2024)
Multiple explanations have been provided as to why individuals with disabilities are so underrepresented in the ‘helping’ professions (e.g., medicine, social work, psychology and more). One possible reason is that as undergraduate students they were less likely to obtain the competitive credentials needed to gain admission to professional programs in such areas, either due to lower ability or lack of sufficient accommodations. The present study assessed the degree to which type and severity of disability, demographic factors (e.g., SES), dispositional factors (e.g., self-esteem), perceived stress, and perceived barriers are predictive of undergraduate students’ ability to obtain such credentials. A survey of 132 North American students suggests that dispositional factors such as the Big Five personality trails of Conscientiousness, Openness and lower Agreeableness, self-esteem and, self-efficacy/self-advocacy, as well as lower disability severity and higher SES are the strongest predictors of success in obtaining competitive post-graduate admission credentials. We propose that, similar to other demographic groups, dispositional factors are the strongest predictors of resilience necessary for academic success.